2020
DOI: 10.1088/1742-6596/1460/1/012084
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alkaline activation on the zeolite binding properties toward dissolved irons

Abstract: This research aims to determine the effect of alkaline activation on the zeolite binding properties toward dissolved irons. Natural zeolite was activated by reflux using NaOH with various concentrations (2 N, 4 N, and 6 N). Furthermore, the activated zeolite was mixed into a solution of FeSO4.7H2O 0.5 M. Zeolite-Fe then characterised using FTIR, XRD, and SEM. The optimum contact time and the adsorption of irons by activated zeolite were studied. The result shows that alkaline activation in zeolite caused a cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…They are the asymmetric vibration band of the O-Si-O or O-Al-O bonds [1]. Asymmetric stretching vibration bands of Si-O or Al-O are also observed at 1052.54 cm -1 , 1045.41 cm -1 , and 1046.84 cm -1 [18]. The shift of the peak to a lower wavenumber is caused by activation with alkaline solutions such that the Si-O-Si and Al-O-Al covalent bonds in the aluminate and silicate groups are affected [18].…”
Section: Functional Group Of Unactivated and Activated Zeolitementioning
confidence: 93%
See 2 more Smart Citations
“…They are the asymmetric vibration band of the O-Si-O or O-Al-O bonds [1]. Asymmetric stretching vibration bands of Si-O or Al-O are also observed at 1052.54 cm -1 , 1045.41 cm -1 , and 1046.84 cm -1 [18]. The shift of the peak to a lower wavenumber is caused by activation with alkaline solutions such that the Si-O-Si and Al-O-Al covalent bonds in the aluminate and silicate groups are affected [18].…”
Section: Functional Group Of Unactivated and Activated Zeolitementioning
confidence: 93%
“…The zeolite mass and yield data in this study are presented in Table 1. The decrease in zeolite yield was due to the dissolution of some metal oxides contained in the pores or channels where base activation is one of the modification techniques that aim to reduce the percentage of silicon (Si) thus that the zeolite has larger pores and becomes more hydrophilic [18,26].…”
Section: The Yield Of Unactivated and Activated Zeolitementioning
confidence: 99%
See 1 more Smart Citation
“…The desiliconization leads predominantly to the removal of silicon from the zeolite body. Figure 2 shows the asymmetric stretch of TO 4 functional group that appears at 900-1250 cm -1 wavenumber (Rahmayani et al, 2020). Asymmetric stretch in ANZ appears at 1042.35 cm -1 wavenumber.…”
Section: Xrf Analysismentioning
confidence: 99%
“…This has led to superior catalytic performance. Rahmayani et al (2020) has activated zeolite by using NaOH at concentration of 2 N, 4 N and 6 N to bind dissolved iron. The study reported that NaOH-activated zeolite can increase the amount of Fe attached to zeolite.…”
Section: Introductionmentioning
confidence: 99%